Patient characteristics associated with retention in an asthma self-management trial for older adults. (3rd August 2022) - Kee, Dustin; O'Conor, Rachel; Wisnivesky, Juan P.; Wolf, Michael S.; Federman, Alex D.
Abstract: Objective: New self-management interventions are being developed for older adults who suffer from worse asthma morbidity than their younger counterparts, but high rates of study drop out have hampered these efforts and there is limited literature on what factors may influence retention in behavioral intervention studies with older adults. This study analyzed illness beliefs and patient characteristics that may contribute to retention in an asthma self-management trial for older adults. Methods: This is a secondary analysis of data from a randomized controlled trial of a self-management support intervention for adults 60 years and older with persistent, uncontrolled asthma. Multivariable logistic regression was used to evaluate the association of medication and illness beliefs, and other subject characteristics with study retention, which was defined as completion of the research study interview at 6 and 12 months. Results: The randomized trial enrolled 388 individuals; 261 (67.3%) completed the 12-month interview. Higher perceived threat of chronic diseases relative to asthma was associated with higher study retention (OR = 1.11, 95% CI = 1.00–1.24) at 12 months. Other variables including asthma beliefs, age, cognitive function, health literacy, and asthma symptoms were not significantly associated with retention. Conclusions: Concern about non-asthma chronic conditions, but no other illness beliefs, or patient characteristics, were associated with retention in an asthma self-management support intervention. Further research, including qualitative studies, is needed to better understand why patients drop out of asthma behavioral intervention studies.